Are user reviews useful for identifying accessibility issues that autistic users face?: an exploratory study - Santiago, Mara Taynar; Marques, Anna Beatriz (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2022: Anais do XXI Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2022)
Google Play Store offers several user reviews that can provide data on aspects of user experience, usability, and accessibility. Several studies address the importance of user reviews and their contributions to the evolution of interactive systems. However, accessibility has been little discussed in this type of study, especially accessibility for users with Autism Spectrum Disorder (ASD). Considering the potential of user reviews, this paper presents a textual analysis of reviews extracted from eight educational applications for autistic children: ABC autismo, Aprendendo com biel e seus amigos, AutApp autismo, Autismo projeto integrar, Jade autism, Matraquinha, OTO (Olhar Tocar Ouvir) and Teacch.me. The analysis adopted the Guidelines for Accessible Interfaces for people with Autism (GAIA) to classify user reviews. An accessibility diagnostic was obtained for apps evaluated and demonstrated that they have recurring accessibility problems regarding responses to actions, visibility of the state of the system, and customization. When compared to studies that have adopted other methods to evaluate the accessibility of the same applications, we observed that the user reviews provided more evidence of accessibility problems.